2021
DOI: 10.1111/rec.13428
|View full text |Cite
|
Sign up to set email alerts
|

Australian native seed sector characteristics and perceptions indicate low capacity for upscaled ecological restoration: insights from the Australian Native Seed Report

Abstract: The Australian Native Seed Sector survey was conducted in 2016–2017 under the auspices of the Australian Network for Plant Conservation. Respondents self‐selected into a seed supply (Seed Collector, Seed Production Area Grower) or seed demand (Seed Purchaser, Other User) group category. Issue statements facing the sector with respect to limiting opportunities for ecological restoration were presented to survey respondents who ranked them in order of importance. Findings revealed that the order of statement imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 31 publications
1
34
0
Order By: Relevance
“…1–5 km) can create logistical difficulties and even ethical conundrums for both suppliers and users, especially if seed from those restricted ranges/provenances is unavailable, limited, rare, of poor quality, or low genetic diversity (Broadhurst et al 2008; Hancock & Hughes 2012; Delpratt & Gibson‐Roy 2015; Nevill et al 2018). This may explain why respondents ranked the statement provenance stipulations are too restrictive at 3.3 (wa) (Gibson‐Roy et al 2021 a ) suggesting many feel local provenance requirements are difficult to meet.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…1–5 km) can create logistical difficulties and even ethical conundrums for both suppliers and users, especially if seed from those restricted ranges/provenances is unavailable, limited, rare, of poor quality, or low genetic diversity (Broadhurst et al 2008; Hancock & Hughes 2012; Delpratt & Gibson‐Roy 2015; Nevill et al 2018). This may explain why respondents ranked the statement provenance stipulations are too restrictive at 3.3 (wa) (Gibson‐Roy et al 2021 a ) suggesting many feel local provenance requirements are difficult to meet.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to develop a more comprehensive snapshot of seed use, the survey explored behaviors around seed ordering and collection/purchase volumes. On ordering, respondents considered seed orders are typically made at too short a notice (Gibson‐Roy et al 2021 a ), but when questioned on practice, findings revealed that both seed demand groups and Seed Collectors marginally nominated forward ordering or collection to order over opportunistic ordering or collection to order, suggesting this perception may not be quite consistent with current behavior.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations